PERFORMA PERTUMBUHAN BUDIDAYA UDANG VANAME SECARA INTENSIF DI JAYA SURUMANA, KABUPATEN DONGGALA SULAWESI TENGAH - Anton; Diana Putri Renitasari,; Budiyati; Yunarty; Mualim (Universitas Sumatera Selatan, 2022)
Whiteleg shrimp technology is growing rapidly. The provision of high stocking density affects the feed management and growth pattern of whiteleg shrimp. The research method used in this research is a survey method with quantitative descriptive data analysis. The observed parameters consisted of FCR, SR, ABW, ADG, ABW and effort analysis. The results of the study were FCR 1.72, SR 25%, ABW increased every day during shrimp rearing, ADG fluctuated. The maintenance period is up to DOC 147. The best harvest period is at DOC 127 because of maximum growth.